The Influence of Implementing the Project Based Learning Model on Students’ Geography Learning Motivation at SMA N 1 Tanjung Mutiara Agam Regency - Valentin, Jane Ridha; Dt. Tanamir, Momon; Febriani, Trina (Journal of Geography Science and Education, 2023)
This research is motivated by the problem of low motivation to study geography, no concentration and low activity during learning, there is no student feedback when learning takes place. The purpose of this study was to find out and analyze data that had the effect of applying the Project Based Learning learning model on increasing students' motivation to learn Geography at SMA N 1 Tanjung Mutiara, Agam Regency. The type of research used was a quasi-experimental research, the research design used was a non-equivalent Control Group Design. The population of all class X students of SMA N 1 Tanjung Mutiara, Agam Regency who were registered in the 2022/2023 school year consisted of 6 classes and the sampling in this study was conducted by random sampling, the instruments in this study were warm and the data analysis techniques were descriptive and inferential statistical analysis. Research results: Is there an effect of applying the Project Based Learning learning model to increasing students' motivation to learn Geography at SMA N 1 Tanjung Mutiara, Agam Regency, research. Based on the descriptive analysis of the experimental class (Project based learning) which obtained a percentage value of 84% in the High category while students in the control class (Conventional) obtained a percentage value of 78% with High. Based on the independent sample t-test regarding student questionnaire answers, it can be concluded that the sig value is 0.002 < 0.05 which states that the coefficient value is significant because tcount > ttable = 3.298 > ttable 1.670, thus it can be interpreted that H0 is rejected and Ha is accepted. so, there is an influence of the project based learning learning model on student learning motivation in the subject of Geography at SMA N 1 Tanjung Mutiara, Agam Regency.